A Budget Impact Analysis of the Introduction of Erythropoiesis Stimulating Agent Subsequent Entry Biologics for the Treatment of Anemia of Chronic Kidney Disease in Canada. Issue 1 (11th November 2014) - Tsao, Nicole W; Lo, Clifford; Leung, Marianna; Marin, Judith G; Martinusen, Dan
Background: In Europe, epoetin subsequent entry biologics (SEBs) have been in use since 2007. Canadian patents of erythropoietin stimulating agents are expiring in 2014, therefore it is predicted that epoetin SEBs will penetrate the Canadian market in the near future. Objective: To estimate the economic impact and costs offsets associated with the uptake and use of one or more epoetin SEBs in Canada for the treatment of anemia in chronic kidney disease. Design: A Canada-wide epidemiological-based budget impact analysis was conducted to estimate cost outcomes under two scenarios: with and without the availability of epoetin SEB. Setting: The analysis was conducted from the perspective of the Canadian healthcare payer, over a 5-year time horizon from 2015 to 2019. Patients: Patients included in the model were those with chronic kidney disease stages 3 to 5, who have renal anemia and require treatment with erythropoietin stimulating agents. Methods: Only direct medical costs pertaining to drug acquisition of currently available erythropoietin stimulating agents in Canada were incorporated in the model. Cost of epoetin SEBs, market shares, uptake rates, and other model inputs were estimated from published sources or databases. No discounting of future costs was applied. Results: Based on our analysis, under market phenomena similar to those seen in the Europe and without considering potential switching from originator epoetin to epoetin SEB, we could expect that Canadian adoption of epoetin SEBs could result in $35 million (2013 CAD, year 1) to $50 million (year 5) cost savings annually, with cumulative savings of $221 million after 5 years. In one-way sensitivity analyses, model variables with substantial impact on cost savings were the prevalence of chronic kidney disease and epoetin SEB uptake rates. Limitations: We did not take into account costs associated with overhead, administration, or adverse events. Conclusion: The advent of SEBs represents an opportunity to relieve financial pressure in our healthcare system. Under the assumption that the efficacy and safety of epoetin SEBs are non-inferior to originator products, we have shown that the adoption of epoetin SEBs can lead to cost savings for the Canadian payer.